Peran Quality Control terhadap Produk Usaha Chika Cake & Bakery di Kota Tarutung - Angelia Putriana; Apriliani Lase; Siti Aisyah; Apriliana Lase (Yayasan Literasi Sains Indonesia, 2023)
Abstract is filled in to briefly describe the entire contents of the article starting from the background, research objectives, research methods, results and conclusions as well as suggestions. Abstract writing must be separate from the article so as not to include references. Abstract is written in 9pt Times New Roman font, maximum 250 words in one paragraphThis study aims to analyze the role of Quality Control (QC) in maintaining and improving the product quality of Chika Cake & Bakery in Kota Tarutung. In an increasingly competitive business environment, product quality is crucial for both customer satisfaction and business sustainability. Quality Control plays a vital role in detecting, preventing, and correcting product defects during the production process, thereby reducing the risk of customer dissatisfaction and post-distribution repair costs. This research employs a case study method with a quantitative approach, collecting data on production volumes and detected defects. Through the application of QC concepts, the study identifies and evaluates the implementation of quality control at Chika Cake & Bakery. The findings are expected to provide insights into the effectiveness of QC in enhancing product quality and offer innovative and sustainable quality control strategies. Consequently, this research not only sheds light on the role of QC at Chika Cake & Bakery but also provides practical guidance for companies to optimize their quality control functions to maintain high-quality standards and remain competitive in a dynamic market.